Adaptive building roof by coupling thermochromic material and phase change material: Energy performance under different climate conditions. (30th November 2020) - Hu, Jianying; Yu, Xiong (Bill)
Highlights: Adaptive building roof, integrated with TC coating and/or PCM layer, is proposed as an energy saving strategy. TC/PCM roof saves up to 17% of total energy use for the building, especially under mild climate. The PCM layer is recommended to place inside the roof insulation. The 5-fold increase in thickness of PCM layer leads to 25% of total energy saving of the building. The 5-fold increase in thickness of TC coating yields 27% of total energy saving of the building. Abstract: Energy transfer in and out through the building envelope plays a prominent role in determining the energy consumption of a building. This study proposes a new paradigm to enhance the energy efficiency of buildings by designing adaptive building roofs that embrace dynamic responses to the fluctuating climatic conditions. Adaptive building roof is designed by integrating with thermochromic (TC) coating and/or phase change material (PCM) layer, namely TC roof, PCM roof, and TC/PCM roof, which could intelligently control both solar energy absorption/reflection and thermal energy transfer in the building. EnergyPlus simulation is implemented to investigate the potential use of adaptive roofs for the building energy saving under five different climatic conditions. The simulation results show that compared to traditional asphalt roof, the TC roof, PCM roof, TC/PCM roof reach total energy saving of up to 13%, 15%, and 17%, respectively. It is also found that TC/PCM roof shows seasonal control of building energy consumption. The sensitivity analysis reveals that when using TC/PCM roof, placing the PCM layer outside the roof insulation has more energy load reduction potential whereas the increase in thickness of PCM layer and TC coating contributes to limited improvement of energy efficiency in the building. Furthermore, adaptive roof is found to perform the best for the building located in the mild climate region. The methodology presented in this study will guide the design of adaptive roof for energy efficient buildings in different climate zones.